2015 IEEE Symposium on Security and Privacy 2015
DOI: 10.1109/sp.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Ad Injection at Scale: Assessing Deceptive Advertisement Modifications

Abstract: Today, web injection manifests in many forms, but fundamentally occurs when malicious and unwanted actors tamper directly with browser sessions for their own profit. In this work we illuminate the scope and negative impact of one of these forms, ad injection, in which users have ads imposed on them in addition to, or different from, those that websites originally sent them. We develop a multi-staged pipeline that identifies ad injection in the wild and captures its distribution and revenue chains. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 13 publications
0
67
0
Order By: Relevance
“…A threshold of 0.3 achieved best precision and recall. are more inclined in targeting the popular browser(s) for ad injections and malversting [48], [51], [30]. As such, for Internet Explorer and Firefox, it may be more beneficial for malicious advertisers, along with presenting malware sites, to expose FLIS users to money laundering scams, adult gaming/video websites, and fraudulent technician services.…”
Section: E Exposing Users To Malware Scam and Adult Websitesmentioning
confidence: 99%
See 1 more Smart Citation
“…A threshold of 0.3 achieved best precision and recall. are more inclined in targeting the popular browser(s) for ad injections and malversting [48], [51], [30]. As such, for Internet Explorer and Firefox, it may be more beneficial for malicious advertisers, along with presenting malware sites, to expose FLIS users to money laundering scams, adult gaming/video websites, and fraudulent technician services.…”
Section: E Exposing Users To Malware Scam and Adult Websitesmentioning
confidence: 99%
“…To analyze malware binaries we used the VirusTotal (VT) service [10], to determine whether the binary had ever been scanned before and whether it was labeled as malicious by an antivirus vendor. To examine malicious Chrome extensions, we leverage the techniques from [48], [51] and manually analyze the behavior of collected extensions in the browser.…”
Section: G Malicious Payloads Investigationmentioning
confidence: 99%
“…If the content injection is also malicious in nature, the publisher's reputation can be further harmed in addition to exposing users to security risks due to malware, phishing, and other threats. Prior work has shown that users exposed to ad injection are more likely to be exposed to "malvertising" and traditional malware [46,48]. Figure 1 gives an overview of ad injection's effect on the normal ad delivery process, while Figure 3 shows an instance of ad injection on amazon.com.…”
Section: Advertisement Injectionmentioning
confidence: 99%
“…A recent line of work has focused on the problem of ad injection via browser extensions. Thomas et al [46] proposed a detection methodology in which, they used a priori knowledge of a legitimate DOM structure to report the deviations from that structure as potential ad injections. However, this approach is not purely client-side and requires cooperation from content publishers.…”
Section: Browser Extension Securitymentioning
confidence: 99%
“…In 2015, a study found 249 Chrome extensions in the Chrome Web store injecting unwanted ads [96]. The authors identified two drops in their measurement of ad injection.…”
Section: Extension Ad Injectionmentioning
confidence: 99%